Co-design of school-based strategies and supports for Aboriginal and Torres Strait Islander youth living with type 2 diabetes: A qualitative study - Stefanie Puszka; Angela Titmuss; Emma Weaver; Natasha Freeman; Marylin Carino; Jade Morris; Peggy Tom; Shiree Mack; Sumaria Corpus; Deanne Minniecon; Peter Azzopardi; James Dowler; et al. (Australian and New Zealand Journal of Public Health)
Objective: Youth-onset type 2 diabetes is an emerging condition impacting Indigenous populations worldwide. Schools have an important role in supporting students to manage their health. Methods: We undertook a qualitative study to (i) explore the lived experience of type 2 diabetes, diabetes management and support in school environments and (ii) co-design recommendations for age-appropriate, culturally safe school-based strategies and supports. Interviews and focus groups were undertaken with Aboriginal and Torres Strait Islander youth, caregivers, health professionals and school-based staff. Aboriginal and Torres Strait Islander youth were involved in determining the research topic. Results: We found a need for school-based measures to address diabetes stigma, medication management, privacy and confidentiality, healthy eating and social and emotional wellbeing and identified further needs for staff training. Conclusions: In many cases, schools are providing extensive support to students, but without adequate resources, supportive systems and policies or staff training, current approaches are insufficient. Implications for public health: Recommendations include whole-of-school responses to address diabetes stigma and to generate sensitive approaches to nutrition, school-based management plans for students with T2D and adoption of Aboriginal and Torres Strait Islander-driven approaches.